(3GdEYdGe h GdYfa GdSjGSj (B/s - (3bLGdj, CefI s ((3YeGf (B:s (3eQcR GdcJGH GdGcGOjej ,s, 2015)
(3eY fgGjI GdbQf GdYQTQjf fLMJ hSGFd GdGJUGd GdLeGgjQ GdMOjKI aj JMbjb fHhI eGchdhgGf Yf GdbQjI GdYGdejI Hd Ef GdHYV jQi GdYGde CUHM eKd Se EHQI agh CcKQ JaGYdG Ydi cGaI GdCUYOI SjGSjG h GbJUGOjG h KbGajG h YScQjG acd GdSjGSGJ JDKQ h JJCKQ HHbjI GdSjGSGJ JDKQ h JJCKQ HHbjI GdSjGSGJ GdCNQi HZV GdfXQ Yf GdecGf Ch GdReGf s
Keywords: (3GdGYdGe s; (3GdYfa GdSjGSjs; (3GdGYdGes; (3GdLRGFQ s